Psychometric adequacy of the Persian adapted version of the Tilburg pregnancy distress scale (P-TPDS) - Leili Salehi; Zoherh Mohmoodi; Fatemeh Rajati; Victor Pop (BMC, 2021)
Abstract Background Pregnancy distress is a combination of anxiety, stress, and depression during pregnancy. The first step in preventing pregnancy distress is to identify women at risk. The present study assessed adaptation and psychometric adequency of the Persian Adapted Version of Tilburg Pregnancy Distress Scale (P-TPDS). Methods By Brislin's translation guidelines, TPDS was translated to Persian. This was followed by determining the face validity of P-TPDS and evaluating construct validity using exploratory and confirmatory factor analyses. The Cronbach's alpha coefficients and intra-class correlation coefficient (ICC) were used to estimate reliability. Results A final 16-item scale was loaded on four distinct constructs jointly accounting for 59.62% of variance. The factors were labelled as delivery-related worries, partner involvement, pregnancy-related worries, and social-related worries. The alpha coefficients for P-TPDS subscales ranged from 0.85 to 0.91 and ICC ranged from 0.70 to 0.77. All comparative indices of the model including CFI, IFI, NFI, and NNFI were above 0.9 showing the goodness of fit for the data with a RMSEA of 0.04, lower bound: 0.038. Conclusions The Persian adapted version of TPDS (P-TPDS) is a reliable and valid scale for assessing pregnancy distress among pregnant women in Iran.